The relationship between cognitive control capacity and language dominance among Malay bilinguals - Ramly, Bazrina; Ngee Thai, Yap; Jalaluddin, Ilyana; Basri, Hamidon (Secholian Publication, 2024)
A growing number of research has suggested that bilingualism could be related to enhanced cognitive control functions (Bialystok & Luk, 2012), because of frequent interference suppression of the first language when a bilingual speaker chooses to speak in the second language and vice versa. Nevertheless, the relationship was not shown in some studies, which raises various questions regarding previous findings. Hence, more studies are done to explore other facets of bilingual speaker’s experience that could modulate the cognitive control functions. Accordingly, the bilingualism threshold is examined to investigate the bilingual benefits. It is suggested that bilingual benefits are not just about knowing two languages, but more so into the usage of the languages possessed. Hence, some studies claimed that balanced language dominance would have better cognitive control capacity. This is a result of the continuous practice of suppressing one language over the targeted language. Therefore, there is a need to look at how language dominance could be related to cognitive control capacity as language dominance may impact the frequency of switching as well as activation of the two languages. This study reports the findings of the relationship between cognitive control capacity and language dominance of Malay bilinguals. The participants of this study were 69 balanced bilinguals and 74 Malay-dominant bilinguals. The Bilingual Language Profile was adopted to measure the language dominance of the participants of this study. Cognitive control capacity of the participants was measured with the Stroop Task. Through a Pearson-correlation analysis, it was found that there is a significant relationship between language dominance and cognitive control capacity. Thus, the findings of this research as in line with previous literatures where language dominance of a bilingual is related to enhanced cognitive control functions.